2018
DOI: 10.1515/cclm-2017-1157
|View full text |Cite
|
Sign up to set email alerts
|

Serum carbohydrate sulfotransferase 7 in lung cancer and non-malignant pulmonary inflammations

Abstract: Serum CHST7 is a promising biomarker for the differentiation between lung cancer and non-malignant pulmonary inflammations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Fewer studies has reported CHST7 was associated with carcinogenic process. A previous literature uncovered that serum CHST7 was significantly increased in all overall stages of primary lung tumors [ 37 ]. In addition, Bi et al reported that methylation level of CHST7 in white blood cells was correlated to colorectal cancer risk [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies has reported CHST7 was associated with carcinogenic process. A previous literature uncovered that serum CHST7 was significantly increased in all overall stages of primary lung tumors [ 37 ]. In addition, Bi et al reported that methylation level of CHST7 in white blood cells was correlated to colorectal cancer risk [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy can also cause stomatitis, sore throat, inflammation of the gastrointestinal mucosa, and liver dysfunction, aggravating the degree of malnutrition (Miyata et al, 2017;Debeljak et al, 2018;Yu et al, 2017;Chao et al, 2017). Some patients therefore refuse treatment or are forced to terminate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The activity-dependent remodeling of CSPGs’ main extracellular matrix (ECM) could be involved in the structural plasticity of the hypothalamo-neurohypophysial system [ 6 ]. Carbohydrate sulfotransferase 7 (CHST7) transfers the sulfate to carbohydrate groups in glycoproteins and involved in carcinogenesis by controlling the biosynthesis of CSPGs [ 7 ]. The CHST7 promoter hypermethylation increased the risk of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The CHST7 promoter hypermethylation increased the risk of colorectal cancer. Serum CHST7 will be used for the differentiation between lung cancer and non-malignant pulmonary inflammation [ 7 ]. The level of CHST7 was noticeably altered in the breast epithelial cell line MCF-10F after parathion treatment, which has a synergistic effect with estrogen [ 8 ].…”
Section: Introductionmentioning
confidence: 99%